Book reviews: Vidyadhar S. Mandrekar; Weak convergence of stochastic processes. With applica- tions to statistical limit theorems, De Gruyter Graduate, De Gruyter, Berlin 2016, vi+141 p., ISBN: 978-3-11-047542-5/pbk; 978-3-11-047631-6/ebook). - LISEI, Hannelore (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
The book is devoted to a detailed study of weak convergence in probability theory with applications to Brownian motion, inference in statistics and convergence in martingale theory.